Hydrologic restoration of anthropoentically altered springs in the Sheldon National Wildlife Refuge in the Great Basin, USA. (April 2023) - Knighton, Leah N.; Petersen, Steven L.; Collins, Gail H.; Allphin, Loreen; Hansen, Neil C.; Johnston, Haley B.; Rader, Russell B.
Abstract: Springbox capped springs divert water for livestock and threaten spring conservation in the Great Basin. Springbox restoration is used to increase water availability at riparian zones and wet meadows. The purpose of our study was to compare six restoration methods used to increase soil moisture. We used a BACI design to compare percent soil moisture before and after restoration at 24 spring sites in Northwestern Nevada, U.S.A. Percent soil moisture was measured at 5-, 15-, 30-, and 45-cm depths during spring and summer months. Year 2017 was wetter than 2016 causing an increase in percent soil moisture in all restoration treatments. Empty springbox cases, cases filled with sand, and caseless gravel-filled springs produced the greatest increase in percent soil moisture at all depths. We recommend sand-filled casings because these funnel water to the surface while sand prevents casing collapse. We recommend sand over gravel because sand is easier to displace as water flows to the surface. The ratio of δ 18 O/d 16 O suggests that springs are fed by shallow groundwater derived from recent precipitation. Inter-annual reductions in precipitation driven by climate change may be the ultimate force determining the preservation of Great Basin spring ecosystems. Highlights: Springbox restoration can recover ecohydrologic processes and riparian communities. We compared five methods for recovering modified springs. Sand filled or empty containers lead to higher soil moisture at all depths. Results assist in improving spring management during a changing climate.